IL‐37 regulates allergic inflammation by counterbalancing pro‐inflammatory IL‐1 and IL‐33. Issue 3 (8th September 2021) - Schröder, Alexandra; Lunding, Lars P.; Zissler, Ulrich M.; Vock, Christina; Webering, Sina; Ehlers, Johanna C.; Orinska, Zane; Chaker, Adam; Schmidt‐Weber, Carsten B.; Lang, Niklas J.; Schiller, Herbert B.; Mall, Marcus A.; et al.
Abstract: Background: Children with asthma have impaired production of interleukin (IL) 37; in mice, IL‐37 reduces hallmarks of experimental allergic asthma (EAA). However, it remains unclear how IL‐37 exerts its inhibitory properties in asthma. This study aimed to identify the mechanism(s) by which IL‐37 controls allergic inflammation. Methods: IL‐37 target cells were identified by single‐cell RNA‐seq of IL‐1R5 and IL‐1R8. Airway tissues were isolated by laser‐capture microdissection and examined by microarray‐based gene expression analysis. Mononuclear cells (MNC) and airway epithelial cells (AECs) were isolated and stimulated with allergen, IL‐1β, or IL‐33 together with recombinant human (rh) IL‐37. Wild‐type, IL‐1R1– and IL‐33–deficient mice with EAA were treated with rhIL‐37. IL‐1β, IL‐33, and IL‐37 levels were determined in sputum and nasal secretions from adult asthma patients without glucocorticoid therapy. Results: IL‐37 target cells included AECs, T cells, and dendritic cells. In mice with EAA, rhIL‐37 led to differential expression of >90 genes induced by IL‐1β and IL‐33. rhIL‐37 reduced production of Th2 cytokines in allergen‐activated MNCs from wild‐type but not from IL‐1R1–deficient mice and inhibited IL‐33–induced Th2 cytokine release. Furthermore, rhIL‐37 attenuated IL‐1β– and IL‐33–induced pro‐inflammatory mediator expression in murine AEC cultures. In contrast to wild‐type mice, hIL‐37 had no effect on EAA in IL‐1R1– or IL‐33–deficient mice. We also observed that expression/production ratios of both IL‐1β and IL‐33 to IL‐37 were dramatically increased in asthma patients compared to healthy controls. Conclusion: IL‐37 downregulates allergic airway inflammation by counterbalancing the disease‐amplifying effects of IL‐1β and IL‐33. Abstract : IL‐37 target cells include many cells involved in asthma pathogenesis such as AECs, DCs, ILC2s, and Th2 cells. IL‐37 limits the pro‐inflammatory and disease‐amplifying effects of IL‐1 and IL‐33 on these target cells. Patients with asthma display increased expression/production ratios of both IL‐1β and IL‐33 to IL‐37. Abbreviations: AEC, airway epithelial cell; DC, dendritic cell; Eos, eosinophil; GC, goblet cell; GM‐CSF, granulocyte‐macrophage colony‐stimulating factor; IL, interleukin; ILC2, innate lymphoid tissue cell 2; Neu, neutrophil; Th2, T helper 2 cell